Determination of serum cadmium and lead in healthy adults from the west of Algeria - Attar, Tarik (SPC Journal of Environmental Sciences, 2019)
Cadmium and lead are ubiquitous and non-biodegradable pollutants representing a great concern to human health. They share common environmental exposure routes through contaminated food, water, and soil. This study was conducted to determine the serum cadmium and lead levels in healthy adults. In the present work, differential pulse anodic stripping voltammetry (DPASV) using a hanging mercury drop electrode (HMDE) was used in order to determine the trace level of cadmium and lead ions in real samples.A populations of one hundred and fifteen healthy adults with a mean concentration of 0.67 Â± 0.31 Âµg.L-1 and 53.11 Â± 3.25 Âµg.L-1 for cadmium and lead were determined, respectively. The accuracy and precision were in agreement with the certified values for both metals by using certified reference materials. Mean serum lead and cadmiumin the current study indicates that in general the population studied here is not exposed to worrisome Pb and Cd levels.Â